Centralized supply chain planning model for multiple forest companies. Issue 3 (2nd July 2016) - Alayet, C.; Lehoux, N.; Lebel, L.; Bouchard, M.
ABSTRACT: In this paper, we present a mathematical model to plan logistics activities in a forest products supply chain. In particular, a mixed-integer linear program is developed to maximize the total profit of the value chain, involving decisions related to the volumes of wood to harvest and to keep in stock, as well as the quantities to deliver to each business unit to meet market demand. The model also includes different constraints concerning fibre freshness across the network (forest, sawmills, and paper mill), as this has an effect on operation costs and supply decisions. Various scenarios based on the demand variation, price fluctuations, and wood aging levels are tested, followed by a sensitivity analysis. Results show that price and demand variations as well as fibre freshness are important criteria to consider in the procurement and production planning for increasing the forest supply chain benefits. The scenarios analysed also confirm the usefulness of the model in guiding companies to make adequate planning decisions according to their business environment.